Pengaruh Kepemimpinan Transformasional, Budaya Organisasi, Keseimbangan Kehidupan Kerja, Terhadap Komitmen Afektif pada Dinas Pengendalian Penduduk dan Keluarga Berencana (PPKB ) Kabupaten Manggarai Barat. - Jinda, Yohanes Mariano Pradana; Subiyanto, Didik (JURNAL MANAJEMEN MOTIVASI, 2026)
This study aims to analyze the influence of Transformational Leadership, Organizational Culture, and Work Balance on Affective Commitment at the Population and Family Planning Control Office (PPKB) of Manggarai Barat. This research is a quantitative study because the approach used includes data collection in the field, data analysis, and drawing conclusions, all of which use aspects of measurement, calculation, formulas, and numerical data. The subjects of the study were all 60 employees of the Population and Family Planning Control Office (PPKB) of Manggarai Barat. Data were analyzed using a linear regression formula. The results of the study indicate that simultaneously Transformational Leadership, Organizational Culture, and Work Balance have a significant effect on Affective Commitment at the Population and Family Planning Control Office (PPKB) of Manggarai Barat.